Importance of piperidone moiety in pharmaceutical chemistry: a review - De, Sourav; Banerjee, Subhasis; Babu, M. Niranjan; Keerithi, C. Navaya (Journal of Applied Pharmaceutical Research, 2015)
Piperidone heterocycle have gained a considerable attention in the field of drug discovery. The wide range of its therapeutic application paved the way to the researchers to insert the nucleus every now and then in diversified pharmacophore, so as to generate novel therapeutic profile. In this review, we have tried to present various therapeutic applications, which have already been demystified by the researchers. The study may prompt the researcher to generate scaffolds of highest therapeutic efficacy considering the importance of 4- Piperidone nucleus.